Top heating 3D fused deposition printing support and preparation method and application thereof

Through the combination of top heating 3D melt deposition printing method and MWCNT@BC/PCL materials, the structural collapse problem of traditional 3D printing technology in complex model printing is solved, and the mechanical properties and bone-promoting ability of PCL scaffolds are improved, achieving efficient bone repair materials suitable for bone tissue engineering.

CN119818727APending Publication Date: 2025-04-15JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046166.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

Smart Images

  • Figure CN119818727A_ABST
    Figure CN119818727A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of hard tissue repair materials, and provides a top heating 3D fused deposition printing stent as well as a preparation method and application thereof. According to the invention, the constructed MWCNT (at) bacterial cellulose (BC) filler is comprehensively researched, and a top heating 3D fused deposition printing technology is adopted, so that the top heating MWCNT (at) BC / polycaprolactone (PCL) scaffold suitable for bone tissue engineering is successfully prepared. The scaffold shows an ideal morphological structure and enhanced mechanical properties, the compressive strength is 85.99 + / -10.03 MPa, the crystallinity is 38.25 + / -0.75%, and the porosity is 54.27 + / -3.10%. The scaffold also shows good hydrophilicity, good biocompatibility, cell adhesion performance, effective in-vitro osteogenesis induction performance and in-vivo mandible repair capability. The invention provides a brand-new and potential solution for clinical treatment of jaw defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hard tissue repair materials, and in particular relates to a top-heated 3D fused deposition printing bracket and a preparation method and application thereof. Background Art

[0002] Mandibular defects are common clinical problems in oral and maxillofacial surgery, which are caused by congenital and acquired factors such as cleft lip and palate, developmental malformations, trauma, tumors, and tooth extraction. Delayed healing or nonunion of these defects can lead to masticatory defects, aesthetic defects, and speech dysfunction. Currently, bone transplantation is the main method for repairing complex bone defects, and traditional bone transplant materials include autologous, allogeneic, and xenografts. Autologous grafts are considered the "gold standard" and have good osteogenic compatibility, but are limited by donor site complications, pain, and availability. Allogeneic grafts use bones from genetically different individuals of the same species, and immunogenicity and viral transmission risks are the main disadvantages. Xenografts use bone tissue from different species to solve the availability of donors, but have similar immune rejection and viral risks. Therefore, researchers have begun to explore tissue engineering bone scaffolds to promote bone reconstruction. The ideal bone scaffold should have good biocompatibility, appropriate porosity, osteoinductivity, biodegradability, and appropriate mechanical properties to support cell adhesion, proliferation, and differentiation. With the advancement of 3D printing technology, bone tissue engineering scaffolds can accurately reproduce the morphology of bone defects, thereby achieving personalized and precise bone repair. Polycaprolactone (PCL) has good biocompatibility, slow degradation, minimal acid decomposition and excellent mechanical properties. However, PCL lacks the osteogenic ability necessary for bone regeneration, and its poor hydrophilicity hinders cell adhesion and limits its application in bone tissue engineering. Therefore, it is feasible to modify PCL with fillers and bioactive agents. Multiwalled carbon nanotubes (MWCNT) are commonly used nanofillers in polymer composites with excellent strength, elasticity, fatigue resistance and osteoinductivity. However, high concentrations of MWCNT may be toxic to human cells. Therefore, how to effectively disperse MWCNT to ensure its safe application in biomedicine is crucial. Carboxylated carbon nanotubes (MWCNT-COOH) are carboxyl groups added to the wall layer of MWCNT, which helps to reduce the cytotoxicity of MWCNT and promote the dispersion of MWCNT. Bacterial cellulose (BC) is a linear polysaccharide connected by β-1-4-glycosidic bonds. It has high porosity, strong mechanical properties, natural three-dimensional network structure, excellent water retention and biocompatibility.

[0003] Common 3D printing techniques, such as stereolithography (SLA), selective laser sintering (SLS) and fused deposition modeling (FDM), can precisely control the structure and mechanical properties of the bracket. The most commonly used 3D printing technology for PCL is FDM, which uses molten thermoplastic PCL filaments as printing materials. The process involves depositing material extruded from a heated nozzle along a path determined by software, building a structure layer by layer, and the molten PCL rapidly cools and solidifies in the air, and fuses to form a bracket. However, when traditional FDM prints complex models with high layer heights, structural collapse often occurs due to inconsistent temperatures between layers, resulting in deformation and printing failure. To this end, the present invention proposes a top-heated 3D fused deposition printing bracket and its preparation method and application. Summary of the invention

[0004] The purpose of the present invention is to provide a top-heated 3D fused deposition printing bracket and a preparation method and application thereof, aiming to solve the problems raised in the above-mentioned background technology.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a top-heated 3D fused deposition printing bracket comprises the following steps:

[0007] S1: carboxylated multi-walled carbon nanotube powder mixed with bacterial cellulose dispersion;

[0008] S2: Add sodium dodecyl sulfate and disperse the mixture by ultrasonic in an ice-water bath for 30 to 60 minutes;

[0009] S3: The mixture was magnetically stirred at 1000 rpm for 1 h at room temperature;

[0010] S4: Ultrasonic dispersion of the mixture in an ice water bath for 4 to 6 h;

[0011] S5: centrifuging the mixture at 15000 rpm for 30 min, discarding the supernatant, and repeatedly washing with deionized water to remove unbound carboxylated multi-walled carbon nanotubes;

[0012] S6: Freeze the mixture at -80°C for 24 hours and then freeze-dry for 48 hours;

[0013] S7: Grind the freeze-dried sample to obtain MWCNT@BC powder;

[0014] S8: sieving the MWCNT@BC powder through a 100-mesh sieve and uniformly mixing it with polycaprolactone;

[0015] S9: The mixture was sent to a mini twin-screw extruder for mixing and uniformly stirred at 110°C before extrusion;

[0016] S10: The mixed material is cut into microspheres and loaded into the feed barrel of the 3D printer;

[0017] S11: Design a bracket cube model according to the target shape and export the STL file;

[0018] S12: preheating the MWCNT@BC / PCL printing ink at a high temperature of 110 to 180° C., and printing the ink using a top-heated 3D fused deposition printing method to obtain a top-heated MWCNT@BC / PCL scaffold.

[0019] Furthermore, the mass fraction of the carboxylated multi-walled carbon nanotube powder is in the range of 0.9 to 1.1 wt %; the mass fraction of the bacterial cellulose is in the range of 15 to 25 wt %; and the mass fraction of the polycaprolactone is in the range of 75 to 85 wt %.

[0020] Furthermore, the concentration range of the sodium dodecyl sulfate is 0.1 to 0.12 mg / ml.

[0021] Furthermore, the printing process of the top-heating 3D fused deposition printing method adopts a layer-by-layer top-heating fused deposition printing method, that is, printing - heating annealing at 25 to 50° C. - printing, to construct a scaffold.

[0022] Furthermore, the printing parameters of the top-heating 3D fused deposition printing method include: layer height 0.25 mm, line spacing 1.2 mm, retraction distance 0.20 mm, platform rise distance 1.0 mm, printing speed 4.0-8.0 mm / s, extrusion speed 0.8-1.0 mm 3 / s, nozzle diameter 0.45mm, platform temperature 2~12℃, annealing temperature 25~50℃.

[0023] A top-heated 3D fused deposition printing bracket prepared according to the preparation method described above.

[0024] An application of the top-heated 3D fused deposition printing bracket described above in the preparation of mandibular defect repair materials.

[0025] An application of the top-heated 3D fused deposition printing scaffold described above in the preparation of bone repair materials.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention proposes a top-heated MWCNT@BC / PCL scaffold, which has good mechanical properties and porosity suitable for bone tissue growth in terms of physical properties. Its compressive strength is as high as 85.99±10.03MPa, the crystallinity is 38.25±0.75%, and the porosity is 54.27±3.10%. In terms of biological properties, the scaffold exhibits good in vitro and in vivo biocompatibility and cell adhesion properties, and has effective in vitro osteogenic induction properties and in vivo mandibular repair capabilities, and is suitable for use in the repair and treatment of maxillofacial bone tissue defects. The present invention adopts a new method to disperse MWCNT on the surface of BC, thereby realizing the manufacture of green, organic solvent-free biofriendly bone scaffolds. In addition, the present invention introduces a top-heated 3D fused deposition printing method, which improves the crystallinity of PCL and increases the mechanical properties of the scaffold, making it more suitable for the repair of maxillofacial bone defects that are subjected to complex mechanical environments such as chewing forces. The scaffold showed good mandibular repair effect through evaluation in rat mandibular defect model, providing new insights into the application of high mechanical strength scaffolds in bone regeneration and remodeling. In summary, the present invention successfully developed a top-heated MWCNT@BC / PCL scaffold, which provides a new and potential solution for the treatment of clinical mandibular defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The Fourier transform infrared spectrum results of 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC; A is a comparison of the infrared spectrum peak results of 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC; B is a schematic diagram of the source of the characteristic peaks of the infrared spectrum of MWCNT@BC.

[0029] Figure 2 The Raman spectra of 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC are shown in Figure I. G / I D It represents the intensity ratio of the G peak and the D peak in the Raman spectrum of MWCNT. The larger the value, the greater the effect of the addition of BC on the structure of MWCNT.

[0030] Figure 3 The results of CCK-8 test on the bioactivity of 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC.

[0031] Figure 4Scanning electron microscope morphology detection images of 0, 0.25, 0.5, 1 and 1.5wt% MWCNT@BC; (ab) are the microscopic morphology of BC after freeze-drying; (c) are the microscopic morphology of MWCNT; (d) are the microscopic morphology of MWCNT and BC after mechanical mixing; (eh) are the microscopic morphologies of 0.25, 0.5, 1 and 1.5wt% MWCNT@BC respectively.

[0032] Figure 5 The results of the live-dead assay of bioactive cells with 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC.

[0033] Figure 6 The results of the biocompatibility hemolysis test of 0, 0.25, 0.5, 1 and 1.5 wt% MWCNT@BC are shown in Figure 1; A is a semi-quantitative detection structure of the degree of hemolysis; and B is a photo of the hemolysis effect.

[0034] Figure 7 The results of alkaline phosphatase detection after 7 and 14 days of osteoinduction of rat bone marrow mesenchymal stem cells (BMSCs) by 0, 0.25, 0.5, 1 and 1.5wt% MWCNT@BC extracts.

[0035] Figure 8 Alizarin red staining results of 0, 0.25, 0.5, 1 and 1.5wt% MWCNT@BC extracts on rat bone marrow mesenchymal stem cells (BMSCs) after 21 days of osteoinduction.

[0036] Fig. 9 Shown are the shear-viscosity test results of MWCNT@BC / PCL and PCL.

[0037] Fig.10 The figure is a schematic diagram of the process of the top heating printer; wherein (a) is the starting state of the printer, (b) is the state where the first layer of the bracket is printed, (c) is the state where the first layer of the bracket is heated, (d) is the state where the second layer of the bracket is printed, (e) is the state where the second layer of the bracket is heated, (f) is the state where the final layer of the bracket is printed, (g) is the state where the final layer of the bracket is heated, and (h) is the final state where printing is completed.

[0038] Fig.11 This is a comparison chart of the effects of top heating printing parameters such as printing speed, nozzle diameter, and whether top heating is used on the morphology of the stent.

[0039] Fig.12These are the X-ray diffraction test results and crystallinity fitting results of top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds; A is the X-ray diffraction test results of the four groups of scaffolds, and B is the crystallinity fitting results of the four groups of scaffolds.

[0040] Fig.13 The scanning electron microscope morphology test results and cross-sectional morphology test results of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold and PCL scaffold; (AD) are the surface morphologies of TOP-MWCNT@BC / PCL, MWCNT@BC / PCL, TOP-PCL and PCL, respectively; (FH) are the cross-sectional morphologies of TOP-MWCNT@BC / PCL, MWCNT@BC / PCL, TOP-PCL and PCL, respectively; (I, J) are high-magnification scanning electron microscope images of the cross-sectional morphologies of MWCNT@BC / PCL and PCL scaffolds, respectively.

[0041] Fig.14 Characterization of the compressive strength of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold; where A is the compressive strength of the scaffold; and B is the compressive stress-strain curve of the scaffold.

[0042] Fig.15 Surface Vickers hardness characterization of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0043] Fig.16 To characterize the hydrophilicity of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0044] Fig.17 It is a characterization of the porosity and pore size of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold; where A is the porosity characterization of the four groups of scaffolds, and B is the pore size characterization of the four groups of scaffolds.

[0045] Fig.18 To characterize the degradation performance of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0046] Fig.19This is the CCK-8 test result of the bioactivity of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0047] Fig. 20 These are the cell live-dead staining results of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0048] Fig.21 The cell adhesion and migration results of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0049] Fig. 22 Quantitative alkaline phosphatase (ALP) detection of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0050] Fig.23 Quantitative analysis of mineralized nodules of top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds.

[0051] Fig.24 The expression levels of osteogenesis-related genes in top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds were detected.

[0052] Fig.25 The expression levels of osteogenic-related proteins of top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds were detected.

[0053] Fig.26 Micro-computed tomography (Micro-CT) characterization results of rat mandibular defect models of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold.

[0054] Fig. 27 HE and Masson section staining of rat mandibular defect models of top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds; A is the HE staining of the rat mandibular defect models of the four groups of scaffolds, and B is the Masson staining of the rat mandibular defect models of the four groups of scaffolds.

[0055] Fig.28HE staining results of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold implanted subcutaneously in rats. DETAILED DESCRIPTION

[0056] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0057] An embodiment of the present invention provides a method for preparing a top-heated 3D fused deposition printed MWCNT@BC filler PCL scaffold, comprising the following steps:

[0058] S1: Carboxylated multi-walled carbon nanotube (MWCNT-COOH) powder is mixed with bacterial cellulose (BC) dispersion; the mass fraction of carboxylated multi-walled carbon nanotube powder ranges from 0.9 to 1.1 wt%; the mass fraction of bacterial cellulose ranges from 15 to 25 wt%;

[0059] S2: sodium dodecyl sulfate (SDS) was added, and the mixture was ultrasonically dispersed in an ice-water bath for 30 to 60 min; the concentration range of sodium dodecyl sulfate was 0.1 to 0.12 mg / ml;

[0060] S3: The mixture was magnetically stirred at 1000 rpm for 1 h at room temperature;

[0061] S4: Ultrasonic dispersion of the mixture in an ice water bath for 4 to 6 h;

[0062] S5: centrifuging the mixture at 15000 rpm for 30 min, discarding the supernatant, and repeatedly washing with deionized water to remove unbound carboxylated multi-walled carbon nanotubes;

[0063] S6: Freeze the mixture at -80°C for 24 hours and then freeze-dry for 48 hours;

[0064] S7: Grind the freeze-dried sample to obtain MWCNT@BC powder;

[0065] S8: sieving the MWCNT@BC powder through a 100-mesh sieve and uniformly mixing it with polycaprolactone (PCL); the mass fraction of polycaprolactone ranges from 75 to 85 wt %;

[0066] S9: The mixture was sent to a mini twin-screw extruder for mixing and uniformly stirred at 110°C before extrusion;

[0067] S10: The mixed material is cut into microspheres and loaded into the feed barrel of the 3D printer;

[0068] S11: Design a bracket cube model according to the target shape and export the STL file;

[0069] S12: Preheat the MWCNT@BC / PCL printing ink at 110-180°C and print it using top-heated 3D fused deposition printing. The printing process uses layer-by-layer top-heated fused deposition printing, i.e., printing - heating annealing at 25-50°C - printing, to construct a top-heated MWCNT@BC / PCL scaffold.

[0070] The printing parameters of the top-heated 3D fused deposition printing method include: layer height 0.25mm, line spacing 1.2mm, retraction distance 0.20mm, platform rise distance 1.0mm, printing speed 4.0~8.0mm / s, extrusion speed 0.8~1.0mm 3 / s, nozzle diameter 0.45mm, platform temperature 2~12℃, annealing temperature 25~50℃.

[0071] One embodiment of the present invention provides the use of the top-heated 3D fused deposition printing scaffold prepared by the above preparation method in the preparation of jaw defect repair materials and bone repair materials.

[0072] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0073] Example 1: A method for preparing a top-heated 3D fused deposition printed MWCNT@BC / PCL scaffold, comprising the following steps:

[0074] S1: 1 wt% MWCNT-COOH powder was mixed with 20 wt% BC dispersion.

[0075] S2: SDS at a concentration of 0.1 mg / ml was added and the mixture was dispersed by ultrasound in an ice-water bath for 30 min.

[0076] S3: The mixture was magnetically stirred at 1000 rpm for 1 h at room temperature (25°C).

[0077] S4: The mixture was dispersed by ultrasonic in an ice-water bath for 4 h.

[0078] S5: The mixture was centrifuged at 15000 rpm for 30 min, the supernatant was discarded, and the mixture was repeatedly washed with deionized water to remove unbound MWCNTs.

[0079] S6: The mixture was frozen at -80°C for 24 h and then freeze-dried for 48 h.

[0080] S7: Grind the freeze-dried sample to obtain MWCNT@BC powder.

[0081] S8: MWCNT@BC powder was sieved through a 100-mesh sieve and uniformly mixed with 79 wt % PCL pellets.

[0082] S9: The mixture was fed into a mini twin-screw extruder for mixing and uniformly stirred at 110 °C before extrusion.

[0083] S10: The mixed material is cut into microspheres and loaded into the feed barrel of the 3D printer.

[0084] S11: Design a 7mm×7mm×10mm rectangular bracket model according to the target shape and export the STL file.

[0085] S12: MWCNT@BC / PCL printing ink was preheated at 140℃ and printed using top-heated 3D fused deposition printing. The printing parameters included: layer height 0.25mm, line spacing 1.2mm, retraction distance 0.20mm, platform rise distance 1.0mm, printing speed 4.0mm / s, extrusion speed 0.8mm 3 / s, nozzle diameter 0.45mm, platform temperature 4℃, annealing temperature 40℃. The printing layer height is 40 layers, and melt extrusion printing-40℃ heating annealing-melt extrusion printing is repeated 40 times to obtain the top-heated MWCNT@BC / PCL scaffold.

[0086] Performance and effect test:

[0087] like Figure 1 As shown in A and B, the MWCNT@BC composite material has a higher -1 The CH stretching vibration peak on MWCNT appeared at 1457 cm -1 The CH bending vibration peak on MWCNT appeared at 1248 -1 、1227cm -1 The COC stretching vibration peak on MWCNT appears. Apart from this, no new functional group characteristic peaks are seen in the infrared spectrum of MWCNT@BC, indicating that MWCNT and BC are physically mixed. -1 The absorption intensity of the OH bending vibration peak at 1055 cm -1 、1025cm -1 The number of stretching vibration peaks decreased, indicating that the alcoholic hydroxyl groups on BC were affected after mixing with MWCNTs. It was speculated that the hydroxyl groups on BC interacted with MWCNTs through hydrogen bonds.

[0088] like Figure 2 As shown in Figure 2, the MWCNT@BC composite material is attributed to the OH stretching vibration peak at 3219 cm-1 It becomes significantly wider, from a sharp peak to 3000cm -1 ~3500cm -1 The short and broad peak at 2913cm indicates that the OH on the surface of MWCNT has changed, and no characteristic peaks related to ester groups and new ether bonds are seen in the Raman spectrum. It is speculated that the OH on the surface of MWCNT has hydrogen bonded with the alcohol OH on BC. -1 The peak intensity of the aromatic CH stretching absorption bands on the left and right gradually decreases and the wavenumber shifts, indicating that the C=C on the MWCNT has changed. Based on the structural inference, π-π adsorption interaction should have occurred.

[0089] like Figure 3 As shown, 1 wt% MWCNT@BC exhibited significantly enhanced activity compared with the BC group.

[0090] like Figure 4 As shown, the freeze-dried BC presents a lamellar layer with an inherent three-dimensional network structure. Figure (a) shows that the freeze-dried BC is in a lamellar state under the low-magnification SEM field of view; as shown in Figure (b) under the high-magnification SEM, its microscopic natural three-dimensional network structure can be seen. As shown in Figures (cd), the undispersed MWCNT-COOH is in a tangled and agglomerated state. As shown in Figure (eh), it can be seen that the dispersed MWCNT-COOH can be evenly spread on the BC surface, and the MWCNTs in the 1.5wt% group are in a stacked and covered state, and curled and entangled MWCNTs can be found in some fields of view. In the 1wt% MWCNT@BC group, it was observed that MWCNTs were rarely stacked, rarely covered and entangled with each other, and the dispersion was better.

[0091] like Figure 5 As shown, the number of dead cells in the 1wt% group was not significantly different from that in the BC group and the control group (Control). According to the GB / T16886.5-2017 standard, the tested compounds were non-cytotoxic.

[0092] like Figure 6 As shown in A and B, hemolysis tests were conducted on MWCNT@BC composites with different mass fractions using rat blood cells. The results showed that the hemolysis rate of MWCNT@BC was less than 1%. It can be seen that the material is biosafe for implantation in vivo.

[0093] like Figure 7 As shown in the figure, in order to evaluate the early and late osteogenic properties of MWCNT@BC, ALP activity was measured on days 7 and 14. On day 7, ALP staining was significant in the 1wt% group. On day 14, the color intensity increased, indicating that MWCNT@BC has a good ability to promote ALP expression.

[0094] like Figure 8 As shown, Alizarin Red S staining showed that the mineralization level of MWCNT@BC in the 1wt% group was significant.

[0095] like Fig. 9 As shown in the figure, the viscosity of MWCNT@BC / PCL printing ink gradually decreases with the increase of shear rate, showing significant shear thinning ability. This indicates its stability and is not easy to settle during the printing process.

[0096] like Fig.10 As shown in (a) to (h), the basic structure of the top heating printer is shown, which is a low-temperature printing platform, a high-temperature extrusion printing nozzle and a temperature-controlled bulb. During the printing process, the platform is cooled to 5°C, and the MWCNT@BC / PCL printing ink is heated to 140°C, and a repeated extrusion printing process of printing-annealing-printing is performed. Fig.10 As shown in (a), the platform is at the lowest position when the printer is in the initial state, and the nozzle and heating lamp are not working; in Figure (b), the printing platform moves up, and the printing nozzle works to complete the printing of the first layer of the bracket; Figure (c) shows the nozzle returning to its position, and the heating lamp heats the first layer of the bracket at a temperature of 40°C; Figure (de) shows the second layer printing and top heating process of the bracket; Figure (fg) illustrates the final layer printing and top heating process of the bracket; Figure (h) shows the final state of the entire bracket after printing.

[0097] like Fig.11 As shown, the optimal printing parameters were determined by comparing the morphology of the bracket: printing speed 4.0mm / s, extrusion speed 0.8mm 3 / s, nozzle diameter 0.45mm, platform temperature 5℃, annealing temperature 40℃.

[0098] like Fig.12 As shown in A and B, the crystallinity of each group of scaffolds was detected by XRD peak fitting method, and the top-heated PCL (TOP-PLC) was about 41.18% ± 0.97%, PCL was 38.68% ± 1.18%, the top-heated MWCNT@BC / PCL (TOP-MWCNT@BC / PCL) was 38.25% ± 0.75%, and MWCNT@BC / PCL was 34.48% ± 0.77%. These results show that top thermal printing significantly improves the crystallinity of the printing ink.

[0099] like Fig.13As shown in (A) to (J), the scanning electron microscope morphology test results (A) show that the top-heated MWCNT@BC / PCL scaffold is arranged regularly, with irregular protrusions visible on the rough surface and regular square pores visible between the lines. Compared with the traditional FDM group shown in Figure (B), the lines of the top-heated MWCNT@BC / PCL group are thicker. As shown in Figure (EF), the fibrous filler morphology can be observed in the cross-section of both. The lateral pores of the top-heated MWCNT@BC / PCL group are obvious, while the upper scaffold structure of the conventional printing group is slightly collapsed. However, considering that the increase in fillers enhances the mechanical properties of PCL, the interlayer pores of the conventionally printed MWCNT@BC / PCL group after cross-section are still more obvious than those of the PCL group. Figure (CD) shows that the surface of the top-heated PCL and the conventional FDM-printed PCL are smooth. Figure (GH) shows that when comparing the cross-sections of the two, the conventional FDM-printed group collapsed under the same printing temperature, while the interlayer pores of the top-heated printing group were observed to be intact. As shown in Figure (IJ), the cross section of the scaffold shows obvious cellulose fillers within the scaffold lines with added MWCNT@BC fillers.

[0100] like Fig.14 As shown in A and B, the compressive strength of the top-heated MWCNT@BC / PCL scaffold (85.99±10.03MPa) was significantly higher than that of the MWCNT@BC / PCL group (62.64±4.32MPa). Similarly, the compressive strengths of the top-heated PCL group and PCL group were 43.24±1.87MPa and 22.75±0.87MPa, respectively. The stress-strain curves also showed that the compression modulus of the top-heated group was stronger than that of the non-top-heated group.

[0101] like Fig.15 As shown, the surface Vickers hardness values ​​of the top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold were 12.72±1.57Hv / kgfmm –2 、8.48±0.71Hv / kgf mm –2 、5.85±0.69Hv / kgfmm –2 and 0.93±0.51Hv / kgfmm –2 . It shows that the micro-Vickers hardness of the top-heated MWCNT@BC / PCL group is significantly higher than that of the other groups.

[0102] like Fig.16As shown in the figure, the water contact angle of the PCL scaffold is 101.75±1.21°, and the water contact angle of the top-heated PCL scaffold is 101.16±1.58°, with no significant difference between the two. However, after adding MWCNT@BC to the PCL scaffold, the water contact angles of the top-heated MWCNT@BC / PCL group and the MWCNT@BC / PCL group decreased to 74.7±0.48 degrees and 76.66±0.48 degrees, respectively. This indicates that the addition of MWCNT@BC significantly reduced the hydrophobicity of PCL, and the top-heated printing method did not significantly change the microsurface of the scaffold.

[0103] like Fig.17 As shown in A and B, the porosity of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold and PCL scaffold were 54.27%±3.10%, 57.33%±2.48%, 53.25%±1.49% and 55.8%±2.60%, respectively, and the pore sizes were 533.3±15.06μm, 570±23.66μm, 563.3±19.66μm and 587.5±10.35μm, respectively, with no significant differences among the groups.

[0104] like Fig.18 As shown, the degradation performance characterization of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold and PCL scaffold within 60 days showed that the weight loss rates of the scaffolds were 2.87%±0.22%, 2.56%±0.12%, 2.25%±0.38% and 1.61%±0.09%, respectively, and there was no significant difference in the degradation levels.

[0105] like Fig.19 As shown in the figure, there was no significant difference in cell viability on the first day among the four scaffold groups of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold. However, on days 2 and 3, the bioactivity of the scaffold containing MWCNT@BC was significantly higher than that of the traditional PCL group, while no significant difference was observed between the top-heated group and the non-top-heated group. This indicates that the addition of MWCNT@BC may promote cell proliferation.

[0106] like Fig. 20 As shown, the live and dead staining results of cells on the scaffold surface after 3 days of growth are shown. In the PCL group, fewer cells adhered to the scaffold surface, which may be because the scaffold surface is relatively hydrophobic, hindering cell adhesion. The top-heated MWCNT@BC / PCL and MWCNT@BC / PCL groups showed more live cells and cell stacking. The number of dead cells in the four scaffold groups was small, and the live cells showed a healthy polygonal morphology, indicating good proliferation performance.

[0107] like Fig.21 As shown in the figure, cells in the top-heated MWCNT@BC / PCL group exhibited an extended polygonal shape. F-actin was orderly and widely distributed throughout the scaffold, and Vinculin staining showed that the cell adhesion structure was widely distributed. In contrast, cells on the surface of the two groups of PCL scaffolds were slender spindle-shaped, with poor diffusion and no obvious organized actin filaments. This shows that the top-heated MWCNT@BC / PCL scaffold promoted cell adhesion.

[0108] like Fig. 22 As shown in the figure, the ALP levels of the scaffolds containing MWCNT@BC were significantly higher than those of the scaffolds containing only PCL at days 7 and 14. The ALP levels of the two highest heating groups (top heating MWCNT@BC / PCL group, top heating PCL group) were significantly higher than those of the traditional FDM printing groups (MWCNT@BC / PCL group, PCL group), indicating that the addition of fillers and the top heating printing method effectively improved the early ALP expression level.

[0109] like Fig.23 As shown, the mineralization level of the top-heated MWCNT@BC / PCL scaffold was significantly higher than that of the other groups at 21 days, indicating that the addition of fillers and the top-heating printing method effectively improved the late cell mineralization level.

[0110] like Fig.24 As shown in the figure, the expression levels of osteogenic-related genes (ColA1, ALP, BMP2, and Runx2) in top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds were detected: In the early stage of osteogenesis, the top-heated printing technology had no significant effect on the expression of Bmp-2 and ALP in the scaffolds without added fillers. However, the top-heated MWCNT@BC / PCL had the highest relative expression of osteogenic genes on day 7, probably due to the combined effects of top heating and MWCNT@BC. Correspondingly, by day 14, the levels of Runx2, ALP, BMP2, and ColA1 in the top-heated MWCNT@BC / PCL group were significantly higher than those in the other groups. And the expression of these four osteogenic-related genes in the top-heated printed scaffolds was higher than that in the ordinary FDM printed scaffolds. It shows that the addition of fillers and the top-heated printing method effectively improve the expression levels of osteogenesis-related genes in vitro.

[0111] like Fig.25As shown in the figure, the expression levels of osteogenic-related proteins in top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds and PCL scaffolds were detected by immunofluorescence. The results showed that the expression levels of BMP-2, RUNX2, OCN and COL-1 in the top-heated MWCNT@BC / PCL and MWCNT@BC / PCL groups were significantly higher than those in the top-heated PCL and PCL groups, indicating that the addition of MWCNT@BC fillers effectively promoted the osteogenic properties of the scaffolds.

[0112] like Fig.26 As shown in Figure 3, the characterization results of micro-computed tomography (micro-CT) of the rat mandibular defect model of top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold showed that new bone formation around the scaffold lines was observed in the rat mandibular defect. By week 4, thin bone bridging extending from the scaffold edge was visible in the PCL group, while the top-heated PCL group showed new bone formation similar to the morphology of the 3D-printed scaffold lines. With the addition of MWCNT@BC filler, the area of ​​new cross-bone formation increased. The top-heated MWCNT@BC / PCL group showed extensive bone formation covering the diameter of the defect. At week 8, the trend of bone tissue area was similar to that of week 4; the bone tissue area of ​​the top-heated MWCNT@BC / PCL group almost completely covered the entire defect. According to the CTAn software analysis, the top-heated MWCNT@BC / PCL, MWCNT@BC / PCL, top-heated PCL, and PCL component fraction (BV / TV) showed a downward trend at the 4th week, indicating that the top-heated MWCNT@BC / PCL had an enhanced osteoinductive effect.

[0113] like Fig. 27 As shown in A and B, the HE and Masson section staining results of the rat mandibular defect model of the top-heated MWCNT@BC / PCL scaffold, MWCNT@BC / PCL scaffold, top-heated PCL scaffold, and PCL scaffold showed that the new bone formation increased in the top-heated MWCNT@BC / PCL and MWCNT@BC / PCL groups, and the bone tissue staining area observed in the top-heated scaffolds was larger than that in the non-top-heated groups. By week 8, the four groups of scaffolds showed similar trends in new bone growth, but the amount of newly formed bone was greater compared with week 4. Masson trichrome staining showed that the collagen arrangement in the PCL group was sparse and disordered, while the collagen arrangement in the top-heated MWCNT@BC / PCL group was denser and stronger, which was consistent with the HE staining results.

[0114] like Fig.28As shown in the figure, the results of HE and immunofluorescence staining of subcutaneous implantation of top-heated MWCNT@BC / PCL scaffolds, MWCNT@BC / PCL scaffolds, top-heated PCL scaffolds, and PCL scaffolds in rats showed that on the third day, the surface of the scaffolds in the four groups were encapsulated by fibrous connective tissue, and immune cells were infiltrated around the scaffolds. Immunofluorescence staining showed early neutrophil infiltration around the scaffolds, and there was no significant difference among the four groups. A large number of macrophages were also detected around the scaffolds. On the third day, the infiltration of M1 macrophages in the MWCNT@BC group was significantly lower than that in the PCL group without fillers. The proportion of M2 macrophages in the MWCNT@BC / PCL group was significantly higher than that in the PCL group without fillers. At this time, there was no significant difference in the inflammation-related factor TNF-α among the groups, suggesting that the addition of MWCNT@BC may promote the polarization of macrophages to the M2 phenotype. By the seventh day, the infiltration rate of M1 macrophages in the MWCNT@BC group was still significantly lower than that in the PCL group without fillers, while the proportion of M2 macrophages was significantly higher in this group. The proportion of M2 macrophages in the top-heated MWCNT@BC / PCL group was significantly higher than that in the MWCNT@BC / PCL group, while the TNF-α level in the MWCNT@BC filler group was significantly lower than that in the non-filler group. By day 14, the proportion of M1 macrophage infiltration in the MWCNT@BC group was significantly lower than that in the PCL group without filler, while the proportion of M2 macrophage infiltration was significantly higher than that in this group. At this stage, there was no significant difference in TNF-α levels between the two groups. These results suggest that the addition of MWCNT@BC may induce macrophage polarization toward the M2 phenotype. This indicates that the top-heated MWCNT@BC / PCL scaffold has good early immune compatibility.

[0115] in conclusion:

[0116] 1. The present invention successfully optimized the performance of the scaffold by selecting an appropriate mass fraction of MWCNT@BC. Through experimental optimization, it was found that this mass fraction not only significantly enhanced the compressive strength of the scaffold without producing cytotoxicity, making the scaffold more stable under load, especially showing significant advantages under the load conditions required for mandibular repair, but also improved the surface bioactivity of the scaffold. The addition of MWCNT@BC provides an ideal microenvironment for the adhesion, proliferation and differentiation of bone cells, further enhancing the osteogenic ability of the scaffold. This material design takes into account both mechanical properties and biocompatibility, achieves a technological breakthrough, and provides a more reliable solution for bone defect repair.

[0117] 2. The top heating 3D printing technology adopted in the present invention significantly improves the crystallinity of the scaffold by regulating the annealing temperature and process parameters of the printing layer, and anneals the printed structure in layers during the layer-by-layer stacking process, thereby enhancing the mechanical properties and stability of the scaffold, and improving the mechanical properties of the scaffold without changing the printing ink. Compared with the conventional FDM group, the microcrystallinity, surface hardness and macro compressive strength of the top heating group are significantly improved. In vivo experiments show that the scaffold optimized by this technology performs well in terms of bearing pressure and maintaining shape integrity, and is particularly suitable for the repair needs of complex bone structures such as the mandible. In addition, the top heating 3D printing technology also has a high customization capability, and can realize personalized design through computer programming according to the specific bone defect of the patient, ensuring that the scaffold is highly matched with the bone defect site, and meeting the mechanical requirements of complex anatomical areas. The present invention introduces the top heating technology and accurately controls the annealing temperature of the printing layer, so that the prepared scaffold not only has enhanced mechanical properties, but also has excellent bone repair function. This innovation brings precision and efficiency changes to scaffold manufacturing, and provides a more competitive solution for the clinical transformation of bone tissue engineering scaffolds.

[0118] Summary: This invention successfully prepared a scaffold material with excellent mechanical properties and bone repair function, namely the top-heated MWCNT@BC / PCL scaffold. This scaffold not only achieves an optimized combination of mechanical properties and biological activity, but also has highly personalized design capabilities, providing an efficient and economical innovative solution for the repair of mandibular bone defects.

[0119] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a top-heated 3D fused deposition printing support, characterized in that: The following steps are involved: S1: carboxylated multi-walled carbon nanotube powder mixed with bacterial cellulose dispersion; S2: Add sodium dodecyl sulfate and disperse the mixture by ultrasonic in an ice-water bath for 30 to 60 minutes; S3: The mixture was magnetically stirred at 1000 rpm for 1 h at room temperature; S4: Ultrasonic dispersion of the mixture in an ice water bath for 4 to 6 h; S5: centrifuging the mixture at 15000 rpm for 30 min, discarding the supernatant, and repeatedly washing with deionized water to remove unbound carboxylated multi-walled carbon nanotubes; S6: Freeze the mixture at -80°C for 24 hours and then freeze-dry for 48 hours; S7: Grind the freeze-dried sample to obtain MWCNT@BC powder; S8: sieving the MWCNT@BC powder through a 100-mesh sieve and uniformly mixing it with polycaprolactone; S9: The mixture was sent to a mini twin-screw extruder for mixing and uniformly stirred at 110°C before extrusion; S10: The mixed material is cut into microspheres and loaded into the feed barrel of the 3D printer; S11: Design a bracket cube model according to the target shape and export the STL file; S12: preheating the MWCNT@BC / PCL printing ink at 110-180°C, and printing the ink using a top-heated 3D fused deposition printing method to obtain a top-heated MWCNT@BC / PCL scaffold.

2. The method for preparing a top-heated 3D fused deposition printing support according to claim 1, characterized in that: The mass fraction of the carboxylated multi-walled carbon nanotube powder is in the range of 0.9-1.1 wt %; the mass fraction of the bacterial cellulose is in the range of 15-25 wt %; and the mass fraction of the polycaprolactone is in the range of 75-85 wt %.

3. The method for preparing a top-heated 3D fused deposition printing support according to claim 1, characterized in that: The concentration range of the sodium dodecyl sulfate is 0.1-0.12 mg / ml.

4. The method for preparing a top-heated 3D fused deposition printing support according to claim 1, characterized in that: The printing process of the top heating 3D fused deposition printing method adopts a layer-by-layer top heating fused deposition printing method, that is, printing - heating annealing at 25 to 50° C. - printing, to construct a scaffold.

5. The method for preparing a top-heated 3D fused deposition printing support according to claim 1, characterized in that: The printing parameters of the top-heating 3D fused deposition printing method include: layer height 0.25 mm, line spacing 1.2 mm, retraction distance 0.20 mm, platform rise distance 1.0 mm, printing speed 4.0-8.0 mm / s, extrusion speed 0.8-1.0 mm 3 / s, nozzle diameter 0.45mm, platform temperature 2~12℃, annealing temperature 25~50℃.

6. A top-heated 3D fused deposition printing bracket prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the top-heated 3D fused deposition printing bracket according to claim 6 in preparing a mandibular defect repair material.

8. Use of the top-heated 3D fused deposition printing scaffold according to claim 6 in preparing bone repair materials.